The Proposed Improvement of Work Posture as An Attempt in Lowering The Risk of Musculoskeletal Disorder - Bambang Suhardi; Fita Permata Sari; Rahmaniyah Dwi Astuti (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2018)
CV Valasindo is furniture industry that produces a wide range of wood product.The production process in CV. Valasindo is devided in two areas, preparation of materials area and production area. This research is focused on work posture of the production area’s workers. The production area itself consists of work stations such as assembly, construction and finishing. The production area was chosen because on the production process in this area is still done manually by the operator. Additionally, on the production area is also still present a series of no ergonomic work posture, both on the work station construction, assembly and finishing. The purpose of this research is to identify a work posture on the production area and doing an improvement to lowers the risk of musculoskeletal injuries. Based on the results of the assessment work posture against 18 work stations at the production area, the seat assembly work station it is known that has the highest risk of musculoskeletal injuries with a score of REBA 9, OWAS 3 as well as score NBM 75. Based on work by posture assessment method of QEC, REBA, OWAS and reinforced with method NBM then the improvement will be focused on work station assembly seat. In this study, the improvements done by designing a working facility in the form of tables and chairs work. Based on the results of the design work facilities have been simulated and the result is the risk of musculoskeletal injuries that used to be high risk decrease to be low